Molecular phylogeny of Nassauvia (Asteraceae, Mutisieae) based on nrDNA ITS sequences - Maraner, Fabrizio (2012)
The phylogeny of the genus Nassauvia and closely related genera was reconstructed using sequences from the internal transcribed spacer regions (ITS) of nuclear ribosomal DNA. The genus Triptilion is nested within Nassauvia, making the latter genus paraphyletic. Neither of the two subgenera Nassauvia and Strongyloma is resolved as monophyletic, and none of the sections of subgenus Nassauvia is recovered as monophyletic. The evolution of the compound secondary inflorescences has been complex in Nassauvia, with the highly aggregated forms representing the original condition in the genus. However, the ancestral condition is equivocal in several clades, and there are alternative reconstructions for the gains–losses of the variously aggregated conditions. There has been at least one gain of solitary capitula in Nassauvia. The evolution of flavonoid chemistry has been complex in Nassauvia, and flavonoids are of limited phylogenetic-taxonomic utility in the genus. Gains–losses of flavonols occur only on terminals whereas changes in flavones and C-glycosyl flavones occur at various levels in the tree. Gains–losses of methylation of flavones and flavonols occur only on terminals.